2009
DOI: 10.1007/s11046-009-9212-x
|View full text |Cite
|
Sign up to set email alerts
|

Candidal onychomycosis: A Mini-Review

Abstract: Onychomycosis is a common fungal infection affecting nails. The primary cause for onychomycosis is dermatophytes, while Candida species have emerged as second-line pathogens. Onychomycosis due to Candida (candidal onychomycosis) is increasingly found in individuals having defective immunity consequential to aging, diabetes mellitus, vascular diseases, HIV infection and drug therapies such as immunosuppressives and broad-spectrum antibiotics. Breached local immunity at the nail complex due to trauma, chronic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 34 publications
6
78
1
5
Order By: Relevance
“…The most cases found in patients aged between 41 and 50 years. Similar observation was reported by Jayatilake et al (2009) who observed that onychomycosis prevalence increases with age reaching its maximum 40-60 years old. On the contrary Grover (2003) reported a high prevalence in the age group of 20-40 years.…”
Section: Discussionsupporting
confidence: 90%
“…The most cases found in patients aged between 41 and 50 years. Similar observation was reported by Jayatilake et al (2009) who observed that onychomycosis prevalence increases with age reaching its maximum 40-60 years old. On the contrary Grover (2003) reported a high prevalence in the age group of 20-40 years.…”
Section: Discussionsupporting
confidence: 90%
“…2,22 Candida species have emerged as second-line pathogens. 23 Onychomycosis is a chronic disease having therapeutic difficulties. In the present study, we have focused the microbiological aspect of onychomycosis, necessary for definitive identification of etiological agents.…”
Section: Resultsmentioning
confidence: 99%
“…Far more than being a simple esthetics problem, infected nail serves as a reservoir of infections of the skin and mucous membrane. Multiple virulence mechanisms of Candida are involved in the pathogenesis of nail infections (reviewed in Jayatilake et al, 2009). …”
Section: Adherence Patterns In Vitromentioning
confidence: 99%
“…For instance, Jayatilake et al (2008Jayatilake et al ( , 2009 have demonstrated that multiple host-fungal interactions such as cavitations, thigmotropism, and morphogenesis take place during candidal tissue invasion.…”
Section: Invasion Capabilitymentioning
confidence: 99%